2018
DOI: 10.1080/17425247.2018.1517747
|View full text |Cite
|
Sign up to set email alerts
|

Clinical translation of immunoliposomes for cancer therapy: recent perspectives

Abstract: Ab: antibody; ADCs: antibody-drug conjugates; API: active pharmaceutical ingredient; ADCC: antibody-dependent cellular cytotoxicity; CR: complete remission; cGMP: current good manufacturing practice; DSPE: distearoyl phosphatidylethanolamine; EGF: epidermal growth factor; EGFR: epidermal growth factor receptor; EPR: enhanced permeability and retention; Fc: fragment crystalline; Tf: transferrin; HACA: human-anti-chimeric antibody; HAHA: human-anti-human antibody; HAMA: human-anti-mouse antibody; HER2: human epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 80 publications
0
36
0
Order By: Relevance
“…Our chosen PLGA-and lipid-based nanoparticle delivery constructs have previously shown in vivo compatibility and biodegradability and are approved for human usage by the US Food and Drug Administration (FDA), making them ideal for clinical application. [37][38][39][40][41] In these studies, we specifically demonstrate improved efficiency for encapsulated PLGA or liposome nanoparticles to deliver our immunogenic BCMA peptide to human dendritic cells, as compared to free peptide alone. Both nanoparticle constructs exhibit uniform size distribution, had similar efficiency of BCMA peptide encapsulation and provide improved peptide delivery to dendritic cells.…”
Section: Discussionmentioning
confidence: 89%
“…Our chosen PLGA-and lipid-based nanoparticle delivery constructs have previously shown in vivo compatibility and biodegradability and are approved for human usage by the US Food and Drug Administration (FDA), making them ideal for clinical application. [37][38][39][40][41] In these studies, we specifically demonstrate improved efficiency for encapsulated PLGA or liposome nanoparticles to deliver our immunogenic BCMA peptide to human dendritic cells, as compared to free peptide alone. Both nanoparticle constructs exhibit uniform size distribution, had similar efficiency of BCMA peptide encapsulation and provide improved peptide delivery to dendritic cells.…”
Section: Discussionmentioning
confidence: 89%
“…However, the first immunoliposome has yet to become approved by the American Food and Drug Administration (FDA) and the European Medicines Agency (EMA) and only few of clinical trials are reported. Limited clinical translation has been proposed to be due to limited tissue distribution and structural instability [ 310 , 311 ].…”
Section: Targeting Cd163 + Macrophagesmentioning
confidence: 99%
“…Since the discovery of Doxil TM [ 73 ], a liposomal-based nanocarrier for doxorubicin (DOX) currently used to treat metastatic breast cancer, liposomes have been the most clinically successful nanocarriers for the treatment of cancer [ 74 ]. Doxil TM , Myocet TM , and Lipusu TM are all liposomal formulations of different chemotherapies approved for breast cancer therapy.…”
Section: Acnps For Breast Cancer Therapymentioning
confidence: 99%
“…Other agents apart from DOX have also been included in ACNPs to treat breast cancer [ 73 , 74 , 75 , 76 , 77 , 78 ]. Similar to the use of DOX, taxanes have demonstrated significant toxicity in normal tissues for breast cancer therapy.…”
Section: Acnps For Breast Cancer Therapymentioning
confidence: 99%